Antioxidant activity of the melanoidin fractions formed from D-Glucose and D-Fructose with L-Asparagine in the Maillard reaction - Echavarría, A. P. (2013)
Melanoidins formed at the last stage of the Maillard reaction have been shown to possess certain functional properties, such as antioxidant activity. In order to gain more insight into these functional properties, soluble model systems melanoidins from L‑Asparagine with D‑glucose or D‑fructose fractionating by ultrafiltration were analyzed. The fractionating/concentration sequence of the melanoidin fraction (1-300 kDa) enabled five fractions to be produced.Additionally, the absorption of melanoidins was measured at different wavelengths (280, 325, 405) and browning at 420 nm. The fractionation effect of melanoidin systems on the color intensity, UV-absorbance scan wavelengths (nm), CIE, L*, a*, b* parameters and antioxidant activity were measured. For this purpose, antioxidant activity was evaluated through the free radical scavenging activity, including 1,1-diphenyl-2-picryl-hydrazil (DPPH) and 2,20-azinobis (3-ethylbenothiazoline-6-sulfonic acid), diammonium salt (ABTS). The results showed that the absorption of the melanoidins formed from Glucose/L-Asn was higher than for those derived from Fructose/L-Asn. On the other hand, their antioxidant power was lower than that for melanoidins formed from Fructose/L-Asn systems.